Examining E-Services and Citizen Engagement for Sustainable Local Governance. Lessons for South Africa in the Post-COVID-19 era - Lewis Edwin Chigova; Costa Hofisi (E-Journal of Humanities, Arts and Social Sciences)
The COVID-19 pandemic underscored the critical role of digital transformation in maintaining essential services and sustaining governance processes. This paper thus sought to examine the nexus between e-services and citizen engagement for sustainable local governance in South Africa during the post-COVID-19 era. It employed a qualitative approach encompassing document analysis and literature review as data collection techniques. The study examined how e-services were utilised for service delivery and citizen engagement during the pandemic and examined their effects on service delivery. The paper highlights that while some local governments made strides in deploying e-services and engaging citizens through digital channels, a considerable portion faced limitations due to digital inequality, lack of infrastructure, and limited digital literacy. Furthermore, the study discusses the key pandemic lessons, including enhancing the responsiveness of e-services mechanisms in local government. The paper strongly recommends a comprehensive approach to digital inclusion, entailing technological access, skills development, and budgetary support, underlining the urgency and importance of this issue. While emphasizing the lessons learned in the post-COVID-19 recovery phase, this research contributes to the discourse on building resilient local governance systems through digital transformation.